2022
DOI: 10.3390/ijerph19020960
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Chest Wall and Diaphragm Proprioceptive Neuromuscular Facilitation (PNF) Techniques in Mechanically Ventilated Patients

Abstract: Physical therapy is part of the treatment for patients admitted to ICU. Proprioceptive neuromuscular facilitation (PNF) is one of the physiotherapy concepts including manual techniques and verbal stimulation. The purpose of this paper is to examine the feasibility of PNF techniques in mechanically ventilated (MV) ICU patients. Another aim is to verify whether the technique using resistance during the patient’s inhalation will have a different effect than the technique used to teaching the correct breathing pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Proprioceptive neuromuscular facilitation (PNF) has gained considerable interest in the field of neurophysiological facilitation of respiration. The presumed physiological mechanisms of PNF include autogenic inhibition, reciprocal inhibition, stress relaxation, and the gate control theory [ 10 , 11 ]. PNF is believed to stimulate proprioceptive receptors in perioral, thoracic, and abdominal muscles as well as sensory inputs from peripheral organs by influencing motor outputs of the central nervous system and stimulating the corresponding nerve reflex, which may help patients develop correct movement patterns [ 12 , 13 ] and induce physiological reactions, such as cough and expectoration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proprioceptive neuromuscular facilitation (PNF) has gained considerable interest in the field of neurophysiological facilitation of respiration. The presumed physiological mechanisms of PNF include autogenic inhibition, reciprocal inhibition, stress relaxation, and the gate control theory [ 10 , 11 ]. PNF is believed to stimulate proprioceptive receptors in perioral, thoracic, and abdominal muscles as well as sensory inputs from peripheral organs by influencing motor outputs of the central nervous system and stimulating the corresponding nerve reflex, which may help patients develop correct movement patterns [ 12 , 13 ] and induce physiological reactions, such as cough and expectoration.…”
Section: Introductionmentioning
confidence: 99%
“…PNF has been an effective strategy for stimulating active breathing, rhythmic initiation, and stabilization [ 10 , 11 ]. Seo and Cho [ 14 ] showed that PNF respiration exercise is effective in increasing expiratory reserve volume and vital capacity and suggested that PNF can improve pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…It gives the respiratory muscles proprioceptive feedback, which triggers reflex respiratory movement responses and enhances the rate and depth of breathing. Repeated compressions are performed to promote an improvement in inspiratory volume, while a stretch response is used to facilitate the onset of inhalation [9]. This effect could lead to a beneficial effect in COVID-19 patients with reduced functional capacity and chest wall mobility.…”
Section: Introductionmentioning
confidence: 99%